Answer:
![(2(x+3))/(x+7)](https://img.qammunity.org/2022/formulas/mathematics/high-school/wjrjjj9edaehteitaaahheor0xx3rryzu1.png)
Explanation:
Given
← factorise numerator and denominator
2x² - 18 ( factor out 2 from each term )
= 2(x² - 9) ← difference of 2 squares
= 2(x - 3)(x + 3)
and
x² + 4x - 21 = (x + 7)(x - 3) , then
=
← cancel common factor (x - 3) on numerator/ denominator
=
![(2(x+3))/(x+7)](https://img.qammunity.org/2022/formulas/mathematics/high-school/wjrjjj9edaehteitaaahheor0xx3rryzu1.png)